Perceptions and Attitudes of Patients About Adult Vaccination and Their Vaccination Status: Still a Long Way to Go? - Ozisik, Lale (Med Sci Monit, 2017)
BACKGROUND: Immunization is one of the most effective public health measures to prevent disease, but vaccination rates in adult populations still remain below the targets. Patient and physician attitudes about vaccination are important for adult vaccination. In this study, we aimed to determine patient attitudes and perceptions about vaccination and the vaccination coverage rates of adult patients in a university hospital in Turkey. MATERIAL/METHODS: A survey was conducted between October 2014 and May 2015 at the Internal Medicine Outpatient Clinics of a university hospital. Adult patients were asked to fill out a questionnaire on their perceptions and attitudes about vaccination and their vaccination status. RESULTS: We interviewed 512 patients ages 19–64 years. Eighty percent of the study population thought that adults should be vaccinated, while only 36.1% of the patients stated that vaccination was ever recommended to them in their adult life. Forty-eight percent of the patients stated that they were vaccinated at least once in their adulthood. The most commonly received vaccine was tetanus vaccine in general, while influenza vaccine was the leading vaccine among patients with chronic medical conditions. While 71.4% of the patients to whom vaccination was recommended received the vaccine, 34.9% of the patients received a vaccine without any recommendation. CONCLUSIONS: Although the vaccine coverage rates among adults in this survey were low, the perceptions of patients about adult vaccination were mainly positive and of many of them positively reacted when their physician recommended a vaccine.